2022
DOI: 10.1021/acsami.2c01302
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Sulfur Leaching for the Development of a Highly Efficient and Stable NiSx/Ni(OH)2/NiOOH Electrocatalyst for Anion Exchange Membrane Water Electrolysis

Abstract: Nickel (poly)­sulfides have been widely studied as anodic catalysts for alkaline water electrolysis owing to their diverse morphologies, high catalytic activities in the oxygen evolution reaction (OER), and low cost. To utilize low-cost and high-efficiency polysulfides with industry-relevant cycling stability, we develop a Ni-rich NiS x /Ni­(OH)2/NiOOH catalyst derived from NiS2/Ni3S4 nanocubes. Ni-rich NiS x /Ni­(OH)2/NiOOH shows improved OER catalytic activity (η = 374 mV@50 mA cm–2) and stability (0.1% volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…This was not only limited to that, but the cathodic shift also compared to the pre-reported 3D Ni 3 S 2 with a similar redox feature at 1.5 V ( vs RHE) revealed a higher affinity to oxidation of the α-NiS over the 3D Ni 3 S 2 . A continuous increase in the current density with the CV cycles at a higher potential range is a clear indication of structural modification, as reported earlier with the Ni electro­(pre)­catalysts . For example, the NiMoO 4 pre-catalyst modifies to NiO and finally to NiO­(OH) under the CV cycles and/or chronoamperometric (CA) conditions, , and a very similar redox feature in the CV was noticed.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This was not only limited to that, but the cathodic shift also compared to the pre-reported 3D Ni 3 S 2 with a similar redox feature at 1.5 V ( vs RHE) revealed a higher affinity to oxidation of the α-NiS over the 3D Ni 3 S 2 . A continuous increase in the current density with the CV cycles at a higher potential range is a clear indication of structural modification, as reported earlier with the Ni electro­(pre)­catalysts . For example, the NiMoO 4 pre-catalyst modifies to NiO and finally to NiO­(OH) under the CV cycles and/or chronoamperometric (CA) conditions, , and a very similar redox feature in the CV was noticed.…”
Section: Resultssupporting
confidence: 75%
“…For example, the NiMoO 4 pre-catalyst modifies to NiO and finally to NiO­(OH) under the CV cycles and/or chronoamperometric (CA) conditions, , and a very similar redox feature in the CV was noticed. Leaching of sulfide from the NiS 2 /Ni 3 S 4 in a mild electrochemical condition was observed only at a 0.1 mA cm –2 current density or at a 1.38 V applied potential . Structural evolution of metal chalcogenides during alkaline OER is established to be the reason of higher electrochemical activity. ,, Shin et al reported the formation of the Ni 3 S 2 /Ni­(OH) 2 heterostructure over the Ni 3 S 2 as the active catalyst toward OER .…”
Section: Resultsmentioning
confidence: 99%
“…The cell temperature was set at 55 °C because the AEM-based cells should be operated at 50-60 °C due to their poor chemical stability, which limits operation at high temperatures for a long period. [94][95][96] The cell was assembled in a cold state, using electrodes (CCS) and membrane which were soaked for 3 h prior to assembly. Then the benchmarking of the single cell measurement protocol started with a cell conditioning step containing 2 h of electrolyte heating at OCV until a steady-state was reached.…”
Section: Methodsmentioning
confidence: 99%
“…Then LSV polarization curve was performed between 1.0 V and 1.7 V vs. RHE at a sweep rate of 5 mV/s. Potentials applied were later extracted manually by the ohmic resistance (iR) drop recorded at the high-frequency region from electrochemical impedance spectroscopy experiments in the frequency range of 0.01 to10 5 Hz at 1.6 V. Cycling stability was evaluated by comparing the LSV curves before and after 1000 cycles at a scan rate of 100 mV/s in the range of 1.0-1.7 V. The chronoamperometric stability was measured by comparing the LSV curves before and after keeping the electrode at a constant potential (1.6 V vs. RHE) for a long period of 20 hours. To determine the ECSA, a series of CV curves were recorded between 1.1 to 1.2 V at various scan rates from 5, 10, 25, 50, 100, 200, to 400 mV/s in 1 M KOH.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The overall energy efficiency of water electrolysis is significantly impeded by the sluggish kinetics of the OER process [2] . To overcome the high overpotential of the OER, numerous electrocatalysts based on non‐precious metals have been developed, especially nickel‐based catalysts due to their dominant catalytic performance and economic requirements [2–5] . The key to successfully identifying the optimal catalyst is to evaluate the catalytical properties of a particular catalyst.…”
Section: Introductionmentioning
confidence: 99%